2016
DOI: 10.1016/j.chemosphere.2016.08.105
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal deposition through rainfall in Chinese natural terrestrial ecosystems: Evidences from national-scale network monitoring

Abstract: h i g h l i g h t sInvestigating heavy metal deposition through rainfall in Chinese natural ecosystem. Precipitation, vehicles number, energy consumption affect heavy metal deposition. Wet heavy metals deposition was positive correlated with soil metals contents. Increasing heavy metals deposition have adverse effects on natural ecosystem. a r t i c l e i n f o a b s t r a c tIndustrialization and urbanization have led to increasingly serious levels of atmospheric heavy metal pollution, which is one of the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 35 publications
(45 reference statements)
1
13
0
1
Order By: Relevance
“…S5), which further confirms that atmospheric deposition results in the accumulation of Cd and Pb in soils. In agreement with our results, Zhu et al (2016) also reported that the Cd and Pb contents in wet deposition were positively related to concentrations in the soils from China's natural terrestrial ecosystems, indicating their atmospheric source. All this evidence suggests that Cd and Pb in the soils of China's mountains suffer from atmospheric deposition, possibly from long-range atmospheric transport.…”
Section: Source Identification Of Trace Metals In the Mountain Soilssupporting
confidence: 92%
“…S5), which further confirms that atmospheric deposition results in the accumulation of Cd and Pb in soils. In agreement with our results, Zhu et al (2016) also reported that the Cd and Pb contents in wet deposition were positively related to concentrations in the soils from China's natural terrestrial ecosystems, indicating their atmospheric source. All this evidence suggests that Cd and Pb in the soils of China's mountains suffer from atmospheric deposition, possibly from long-range atmospheric transport.…”
Section: Source Identification Of Trace Metals In the Mountain Soilssupporting
confidence: 92%
“…Results showed that the atmospheric deposition rates around the BS and NYS were lower than those measured in the Pearl River Delta (Wong et al, 2003), North China (Pan and Wang, 2015), Beijing (Guo et al, 2017), and agro-ecosystems in China (Zhang et al, 2017b). However, these deposition rates were comparable with the deposition levels monitored in the Jiaozhou Bay and in several Chinese terrestrial ecosystems (Xing et al, 2017;Zhu et al, 2016). The detailed results of the comparisons are presented in Table S12 of SI.…”
Section: Atmospheric Deposition Ratesmentioning
confidence: 79%
“…With regard to AWD of TMs in remote regions, Tripathee et al found that many TMs (Cr, Co., Ni, Cu, Zn, Cd and Pb) were significantly enriched in precipitation in central Himalayan regions owing to the long-range transport of these elements [19]. Zhu et al revealed that wet heavy-metal deposition was significantly correlated with the level of industrial development, traffic volume, and energy consumption [8]. These studies were mainly concentrated in ecologically sensitive regions, such as large and medium cities, coastal waters, inland lakes, and remote ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…TMs in the atmosphere mainly originate from anthropogenic activities, e.g., fossil fuel combustion, road dust, smelting, construction dust, biomass burning, and waste incineration, and easily concentrate in atmospheric fine particles [7]. These particles transport TMs to remote regions, including as far as the Arctic, via atmospheric circulations [8][9][10]. Compared with try deposition, by which TMs can directly remove from atmosphere with airbone particles, atmospheric wet deposition (AWD) through precipitation is considered to be the major pathway for removal of TMs from the atmosphere [11]; therefore, it is of great significance to quantify their fluxes, identify their sources, and assess their potential effects on ecosystems and human health.…”
Section: Introductionmentioning
confidence: 99%